(untitled) (Notes in Current Biology, 2016)
The article analyzes the dynamics of prevalence of congenital malformations in newborns in the face of shrinking urban population of reproductive age. Due to the long negative natural and migration growth, raising the level of endogamy and reduce genetic mating distance, while strengthening intra-population genetic diversity by increasing the proportion of interethnic marriages (from 35,5 to 50,5 %) is stabilizing the population frequency of congenital malformations of newborns, including hereditary forms.